Cervical Fibrosis as a Predictor of Dysphagia. (6th July 2020) - Nachalon, Yuval; Nativ‐Zeltzer, Nogah; Evangelista, Lisa M.; Dhar, Shumon I.; Lin, Sharon J.; Shen, Shih C.; Belafsky, Peter C.
Abstract : Objective: Radiotherapy of head and neck cancer (HNCA) causes dysfunction through radiation‐induced fibrosis (RIF). We hypothesize that the degree of cervical fibrosis is associated with swallowing dysfunction. This study evaluated the association between cervical fibrosis and swallowing dysfunction in patients after radiation therapy for HNCA. Study Design: Cross sectional study. Methodology: A convenience sample of patients with dysphagia who were at least 1 year post radiation therapy for HNCA underwent simultaneous cervical ultrasound (US) and video‐fluroscopic swallow study (VFSS). US determinants of fibrosis were measurements of sternocleidomastoid fascia (SCMF) thickness bilaterally at the level of the cricoid. Primary and secondary outcome variables on VFSS were pharyngeal constriction ratio, a validated measure of pharyngeal contractility, and penetration aspiration scale (PAS). A qualitative assessment of lateral neck rotation was performed as a functional measure of neck fibrosis. Results: Simultaneous cervical US and VFSS examinations were performed on 18 patients with a history of radiotherapy for HNCA and on eight controls. The mean (±SD) age of the entire cohort (N = 26) was 66 (±10) years. Individuals with a history of radiation had significantly thinner mean SCMF (0.26 [±0.04 mm]) compared to controls (0.48 [±0.06 mm]; P < .05). Individuals with thinner SCMF were more likely to have moderate to severe restriction in lateral neck rotation, a higher PCR, and a higher PAS ( P < .05). Conclusion: Thinner sternocleidomastoid fascia on ultrasound in patients having undergone radiotherapy for head and neck cancer was associated with reduced lateral neck movement, poorer pharyngeal constriction and greater penetration/aspiration scale. The data suggest that cervical fibrosis is associated with swallowing dysfunction in head and neck cancer survivors and support the notion that, "As the neck goes, so does the swallow." Level of Evidence: 3. Laryngoscope, 131:548–552, 2021